Cancer during pregnancy: A qualitative study of healthcare experiences of Australian women. (10th February 2021) - Stafford, Lesley; Sinclair, Michelle; Gerber, Katrin; Collins, Leah; Newman, Louise; Saunders, Christobel; Ives, Angela; Mason, Kylie D.; Peate, Michelle; Lippey, Jocelyn; Umstad, Mark P.; Shanahan, Kerry; et al.
Abstract: Objectives: To identify features enhancing the quality of healthcare experiences for women with gestational cancer, and explore the impact of the heterogeneous Australian healthcare system on those experiences. Methods: Semi‐structured, qualitative interviews were conducted with women diagnosed with any cancer during pregnancy in the last five years. Recruitment occurred during 2018–2019 via social media and professional, clinical and community networks. Questions related to women's experiences of their healthcare, wellbeing and psychosocial needs. Interviews were analysed thematically. Results: Study participants ( n = 23) received treatment in the private sector ( n = 10), public sector ( n = 8), or both ( n = 5). Five interview themes were found: Control over healthcare ; Trust in clinicians, hospitals and systems ; Coordination of care ; An uncommon diagnosis ; Holistic, future ‐ oriented care . Women were most likely to have had a positive healthcare experience when (a)care was well‐coordinated and adjusted to meet their unique needs/challenges, and (b)women perceived their care went beyond their immediate medical needs and encompassed future psychosocial wellbeing, including preparation for postpartum challenges. Conclusion: Existing 'usual care' in the public and/or private sector for both the pregnancy and the cancer is insufficient to meet these women's needs. Prioritising psychological wellbeing including psychosocial needs, and communication and planning around fertility and postnatal challenges are essential for this population.